Revascularization of Lower Extremity Chronic Total Occlusions With a Novel Intraluminal Recanalization Device: Results of the ReOpen Study. (February 2014) - Bosiers, Marc; Diaz-Cartelle, Juan; Scheinert, Dierk; Peeters, Patrick; Dawkins, Keith D.
Purpose: To report outcomes of a multicenter, nonrandomized study evaluating the safety and effectiveness of a guidewire-mounted mechanical recanalization device with a rotating distal tip (TruePath) in facilitating the crossing of infrainguinal chronic total occlusions (CTOs). Methods: Eligible patients had lower extremity ischemia and an angiographically confirmed occlusion, with no antegrade flow for at least 30 days, in an infrainguinal artery. Enrollment occurred when a previous or concurrent attempt to cross the CTO with a conventional guidewire had failed. A total of 85 patients with 85 lesions were enrolled; 61 (71.8%) target lesions were in the superficial femoral artery and 68 (80%) were considered moderately or heavily calcified. Clinical evaluations were assessed immediately post procedure and at 30-day follow-up. Results: Freedom from clinical perforation at the time of the procedure was achieved in 98.8% of patients. The device facilitated CTO crossing into the distal true lumen (technical success) in 68 (80.0%) patients, with subsequent distal guidewire positioning in 65 (76.5%). The average ABI (n=58) improved from 0.65 (range 0.35–1.20) at baseline to 1.00 (range 0.50–2.00) through 30-day follow-up. Symptoms improved in 70 (82.4%) patients upon treatment, and improvement was maintained in 57/70 (81.4%) through 30 days. Conclusion: The ReOpen Study demonstrated that the TruePath device is safe and effective for facilitating crossing of CTOs resistant to conventional guidewire maneuvers.